Intolerance of uncertainty predicts altered threat expectancy ratings during reinstatement. Issue 3 (14th August 2022) - Zuj, Daniel V; Dymond, Simon; Murray, Stuart B; Thomas, Shaima; Morriss, Jayne
Intolerance of uncertainty (IU) is a transdiagnostic risk factor for psychiatric disorders, and plays an important role in fear and threat learning under uncertainty. The 'reinstatement of fear/threat' is an understudied phenomenon thought to represent clinical symptom relapse. Reinstatement of conditioned responding can be captured in the laboratory by presenting unsignaled presentations of an aversive unconditional stimulus. The present study investigated IU as a predictor of reinstatement effects, such that individuals higher in IU, relative to lower IU, would show larger reinstatement. Sixty-two participants completed the Intolerance of Uncertainty Scale and provided threat expectancy ratings (i.e. certainty of receiving a shock) during a differential threat conditioning and extinction paradigm with reinstatement. Findings suggested a differential increase in threat expectancy ratings to both the threat and safety cue following reinstatement, although this effect was small and did not survive follow-up tests. Nevertheless, IU was a significant predictor of reinstatement to the threat cue but not the safety cue, although this effect was not in the expected direction. Specifically, higher IU was associated with reduced threat expectancy ratings post-reinstatement. These findings provide support for the limited literature demonstrating an important role for IU in reinstatement effects and should be investigated further.